Sex-specific comparison of clinical characteristics and prognosis in Crohn’s disease: A retrospective cohort study of 611 patients in China - Liu, Zhaoshi; Bai, Xiaoyin; Zhang, Huimin; Wang, Zheng; Yang, Hong; Qian, Jiaming (Frontiers in Physiology, 2022)
Background: Real-world data on the impact of sex on the disease progression and prognosis of Crohn’s disease (CD) from large-scale Chinese cohorts are lacking. Aims: This study aimed to evaluate sex disparities in the clinical characteristics of, disease progression behaviours of and surgery-related risk factors for CD. Methods: A retrospective cohort study comprising 611 patients consecutively diagnosed with CD at Peking Union Medical College Hospital from January 2000 to December 2020 was conducted. Multivariate Cox regression and survival analyses was performed to assess the risk factors for disease progression and CD-related surgery in sex subgroups. Results: Male sex was an independent protective factor against multisystemic extraintestinal manifestations [EIMs] (HR: 0.52, p = 0.03) and a risk factor for intestinal perforation (HR: 1.85, p = 0.01). Male patients had longer EIM-free survival (p = 0.024) and shorter intestinal perforation-free survival (PFS) than females (p = 0.012). Of the 397 patients with the A2 classification, male patients had a higher risk of CD-related surgery (HR: 1.80, p = 0.028) and shorter surgery-free survival (SFS) than female patients (p = 0.04). Conclusion: Sex disparities in disease progression and outcomes of CD were revealed in a single Chinese centre. Male sex was independently associated with worse disease progression and prognosis including multisystemic EIMs and perforation, which suggests the need for individualized management according to risk classification.